Classroom social networks, students' peer-related social experiences and sense of belonging: The specific case of students with SEN - Freire, S.; Roçadas, C.; Pipa, J.; Aguiar, C. (British Educational Research Journal, 2024)
One main argument for inclusion refers to the social benefits that students with SEN might have from being in contact with typically developing classmates. Students' sense of belonging to the classroom is also a relevant dimension of inclusion, given its importance for positive emotional and social development and academic motivation. Yet, studies specifically focused on students with SEN show mixed results regarding their sense of belonging. While some studies have highlighted the effect of classroom social networks on peer-related social experiences, to our knowledge no study has examined its effect on the sense of belonging. Thus, the goal of the current study is to examine the associations between the structure of classroom social networks, peer-related social experiences in the classroom and the sense of belonging of students with and without SEN. The participants were 914 students (56% boys, 10% SEN, average age 12.68) attending Portuguese schools. Contrary to what was expected, although students with SEN were, on average, more rejected and less accepted by the peer group than students without SEN, they did not differ in their levels of sense of belonging. In addition, the structure of classroom social networks was associated with students' belonging in unexpected ways. Results point to the importance of creating social conditions in the classroom to facilitate positive peer interactions and relationships, and the need for teachers to pay attention to the social structure of the classroom in order to create a positive atmosphere where all students feel accepted, respected, valued and a part of the classroom.